2020
DOI: 10.1101/2020.09.30.281055
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transgenic pyrimethamine resistantPlasmodium bergheias a model forin vivoanti-DHFR drug testing

Abstract: Inhibitors for Plasmodium falciparum dihydrofolate reductase (DHFR) form an important class of antimalarial drugs widely used for malaria treatment, but have been compromised by development of resistance to the drugs. Mutations in DHFR are the main contributing factors to the resistance. Although new, rationally designed antifolates active against resistant P. falciparum, such as P218, have been developed, the activity against the quadruple mutant P. falciparum (V1/S) has only been demonstrated in vitro, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…This study sought to characterize antifolates as chemopreventive antimalarial drugs, especially against the quadruple mutant Pfdhfr parasite. Using the transgenic P. berghei harboring quadruple mutant Pfdhfr in place of the wild-type Pbdhfr as an in vivo antifolate resistant model, we demonstrated that the quadruple mutation on Pfdhfr does not only leads to PYR treatment failure (Koonyosying et al, 2020) but also confers complete resistance to PYR chemoprevention. Antifolates of the previous generation are then no longer effective for both applications in most malaria endemic areas, thus prompting the development of alternative treatments.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study sought to characterize antifolates as chemopreventive antimalarial drugs, especially against the quadruple mutant Pfdhfr parasite. Using the transgenic P. berghei harboring quadruple mutant Pfdhfr in place of the wild-type Pbdhfr as an in vivo antifolate resistant model, we demonstrated that the quadruple mutation on Pfdhfr does not only leads to PYR treatment failure (Koonyosying et al, 2020) but also confers complete resistance to PYR chemoprevention. Antifolates of the previous generation are then no longer effective for both applications in most malaria endemic areas, thus prompting the development of alternative treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of having a well-known target allows characterization of resistance mechanism and rational design of new classes of antifolates that can overcome the resistance (Yuthavong et al, 2012). Although the new class of antifolates such as P218 can inhibit asexual stage and male gametocyte exflagellation of quadruple mutant parasites (Koonyosying et al, 2020;Posayapisit et al, 2021;Yuthavong et al, 2012), the information on how potent these new compounds are for the chemoprevention activity against quadruple mutant parasite has never been experimentally demonstrated due to the lack of reliable liver stage model of the resistant parasite.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations